Verbum mirificum - Rousse-Lacordaire, Jérôme (Revue des sciences philosophiques et théologiques, 2004)
Thomas Anshelm, first-rate humanist printer, integrated into two of his markers a very particular Hebrew name, YHSWH, which gave rise to numerous explanations, at times altogether fanciful. The purpose of this study is to show the source - the Christian cabalist Reuchlin’s speculations upon the divine names - and the signification for Anshelm: an occult Christian perspective of deification by the invocation of the all-powerful name of Jesus.